PELATIHAN MITIGASI BENCANA GELOMBANG EKSTRIM DAN ABRASI PANTAI DI SMAN 7 LUWU - Jusmi, Fitri; Tenriawaru, Eka Pratiwi; Cambaba, Sunarti (Universitas Mataram, 2024)
SMAN 7 Luwu is one of the schools in Luwu Regency where most of the students come from coastal areas. Therefore, efforts are needed to increase community preparedness for coastal erosion disasters. This service activity aims to provide knowledge to SMAN 7 Luwu students regarding mitigation of extreme wave disasters and coastal erosion so as to increase their awareness of disasters. The method of implementing activities begins with preparing the materials and instruments to be used, then continues with the implementation stages at school. There are 3 materials given to students, namely: (1) introduction to disasters, (2) mitigation’s education of extreme waves and (3) mitigation of beach abrasion. The results obtained were 20 students of class XII in SMAN 7 Luwu who took part in the activity. These students live in coastal areas. The students felt enthusiastic about paying attention to the presentation of the material and asked questions and provided answers to the speaker’s questions.